Exploring the Role of Food Security in Stunting Prevention Efforts in the Bondowoso Community, Indonesia - Gunawan Prayitno; Aidha Auliah; Lilik Zuhriyah; Achmad Efendi; Syamsul Arifin; Rahmawati Rahmawati; Achmad Tjachja Nugraha; Enock Siankwilimba (Societies)
Stunting—defined by the World Health Organization as a height-for-age z-score < −2 SD—signals chronic undernutrition that impairs both physical and cognitive development. This study investigates how the three pillars of food security (availability, access, utilization) influence stunting prevention efforts in the Bondowoso Regency, East Java, Indonesia. A cross-sectional survey of 113 mothers of stunted children (0–59 months) was analysed with Structural Equation Modelling using Partial Least Squares (PLS-SEM). The model reveals significant positive paths from food security pillars to composite stunting prevention behaviours (β = 0.18–0.86, p < 0.05), with availability emerging as the strongest predictor. These findings highlight food security as a lever for reducing the local stunting prevalence (local 32% vs. national 24.4%) and provide evidence for community-based nutrition programmes in similar agrarian districts. Strengthening food security is therefore essential to safeguarding child well-being in vulnerable Indonesian communities.